Efecto de aplicación de biosólidos sobre las propiedades físicas de un suelo cultivado con caña de azúcar (2013)
The effects of the biosolids applications on physical properties (bulk density, porosity and soil structural stability) in a soil of sugarcane crop and crop yield were evaluated. The experiment was carried out in the in the Cañaveralejo wastewater treatment plant at Cali, Colombia using a randomized complete block experimental design, two replications and eight treatments: (soil without biosolids application and without mineral fertilization (To), and soil with mineral fertilization (FM)), and six treatments with biosolids application to 100% and 200% of the dose required nitrogen by the crop as follows: BD100-BD200 dehydrated biosolids, BST100-BST200 thermally dried biosolids, and BA100-BA200 alkalinized biosolids. Results showed that significant differences were not found in soil physical properties and crop yield but trends to decrease the values of bulk density (1.33 Mg m-3 to 1.29 Mg m-3) and microporosity (48.8% to 45.8%), and to increase the values of structural stability (1.8 mm to 3.1 mm) and macroporosity (2% to 5%) were identified, which favor the water-air relation in the soil.